A Model for Developing Cultural and Civic Literacy as a Means of Character Habituation Among Students at Public Elementary Schools in Pulubala Subdistrict, Gorontalo Regency - Side, Ismail Y; Ngiu, Zulaecha; Cuga, Candra (Journal of Basic Education Research, 2026)
Purpose of the study: This study aims to develop a cultural and civic literacy model based on character habituation that is systematically integrated into the learning process, in order to address the dominance of reading–writing and numeracy literacy, and to strengthen the sustained internalization of values in the character development of elementary school students Methodology: This study employed a Research and Development (R&D) method using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The research subjects included students and teachers from three public elementary schools in Pulubala Subdistrict, Gorontalo Regency. Data were collected through observation, interviews, questionnaires, and documentation, and analyzed using descriptive qualitative and quantitative techniques, with effectiveness tested using the N-Gain score Main Findings: The results indicate that the implementation of cultural and civic literacy in elementary schools remains fragmented and is not yet supported by systematic instructional design. Based on needs analysis, students require contextual, simple, visually-based learning that is integrated with local culture. The developed model, LITBUD-KAR, has a very high level of validity (>92%), practicality, and user acceptance (>96%), and is effective in increasing student engagement, understanding of cultural and civic values, and character development, with an N-Gain value of 0.75 (high category) Novelty/Originality of this study: The novelty of this study lies in the development of a cultural and civic literacy model based on character habituation, which is systematically integrated across intracurricular, co-curricular, extracurricular, and school culture dimensions.